Island remodelling in acute and chronic aortic dissection treated with frozen elephant trunk. (24th February 2023) - Dohle, Daniel-Sebastian; Mattern, Leon; Pfeiffer, Philipp; Probst, Chris; Ghazy, Ahmed; Treede, Hendrik
Abstract: OBJECTIVES: The island technique for reimplantation of supra-aortic vessels in frozen elephant surgery is commonly used but might be questioned for dissected vessels. This study analyses the remodelling of reimplanted supra-aortic vessels after FET in acute and chronic aortic dissection (CAD). METHODS: Between June 2017 and April 2021, 133 patients were operated for acute and CAD using the frozen elephant technique. The island technique for reimplantation of the supra-aortic vessels was used in 94/133 patients. In 68 acute and 21 chronic patients, the total vessel lumen (VL), true lumen, false lumen (FL) and perfused FL area were measured in the innominate, right common carotid and left common carotid artery. Relative luminal changes were compared. RESULTS: In acute aortic dissection, 80% innominate, 40% right carotid and 59% left carotid arteries were dissected preoperatively, but postoperatively FL was only patent in 29%, 12% and 10% ( P  < 0.001). FL disappearance resulted in >20% total VL reduction in innominate, right carotid and left carotid artery ( P  < 0.01). In CAD, only 38% innominate, 14% right carotid and 43% left carotid arteries were dissected preoperatively, but postoperatively FL was patent in 19% (ns), 10% (ns) and 5% ( P  = 0.009). CONCLUSION: Vascular remodelling is frequently found after the island technique. In acute aortic dissection, the island technique frequently initiates FL disappearance associated with VL decrease. Continuously dissected head vessels show positive remodelling with true lumen increase without VL increase. FL disappearance is frequently found in CAD. Abstract : Nowadays, the therapy of acute and chronic aortic dissections (CAD) is hardly conceivable without the option of using a frozen elephant trunk well selected for true lumen (TL) stabilization in cases of malperfusion or for prognosis in young, clinically stable patients [1].